The Crosstalk Between Hippo-YAP Pathway and Innate Immunity - Wang, Shuai; Zhou, Lili; Ling, Li; Meng, Xuli; Chu, Feng; Zhang, Suping; Zhou, Fangfang (Frontiers in Immunology, 2020)
Recognition of pathogen-associated molecular patterns (PAMPs) triggers expression of antiviral interferons and proinflammatory cytokines, which functions as the frontier of host defense against microbial pathogen invasion. Hippo-YAP pathway regulates cell proliferation, survival, differentiation and is involved in diverse life processes, including tissue homeostasis and tumor suppression. Emerging discoveries elucidated that the components of Hippo-YAP pathway, such as MST1/2, NDR1/2 and YAP/TAZ played crucial regulatory roles in innate immunity. Meanwhile the innate immune signaling also exhibits regulatory effect on Hippo-YAP pathway. As for the importance of these two pathways, it would be interesting to figure out the deeper biological implications of their interplays. This review focuses on the regulation between Hippo-YAP pathway and innate immune signaling. We also propose the possible contribution of these interplays to tumor development.